Sara Crewe; Or, What Happened at Miss Minchin's Boarding School - Burnett, Frances Hodgson, 1849-1924 (Salt Lake City, UT : Project Gutenberg, 2006)
"Sara Crewe; Or, What Happened at Miss Minchin's Boarding School" by Frances Hodgson Burnett is a novel written during the late 19th century, falling within the Victorian era. The story explores themes of resilience, social class, and imagination as it follows a young girl named Sara Crewe who faces the harsh realities of life at a boarding school after losing her father and her fortune. The novel presents a critique of social injustice while highlighting Sara's indomitable spirit and her ability to maintain her identity and kindness despite her circumstances. The narrative centers on Sara Crewe, a bright and imaginative girl raised in India by her father, a wealthy captain. After her father passes away and her fortune is lost, Sara is forced to live in the attic of Miss Minchin's boarding school, where she is mistreated and reduced from a favored pupil to a servant. Despite her struggles, Sara maintains her grace and optimism through her vivid imagination, often envisioning herself as a princess. Throughout the story, her kindness and compassion for others, including a beggar child she encounters, ultimately lead to a transformative turn of events when her father's friend discovers her plight. The novel culminates in Sara regaining her fortune and finding a loving guardian, illustrating the triumph of goodness and resilience over adversity. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Little_Princess
Release date is 2006-03-08
Produced by Judith Boss and David Widger
Keywords: Orphans -- Juvenile fiction; Schools -- Juvenile fiction; Boarding schools -- Juvenile fiction; Girls -- Juvenile fiction; London (England) -- Juvenile fiction